A simple doping strategy to improve PEDOT:PSS charge extraction capability in polymer solar cells. (15th November 2022) - Wang, Zhongqiang; Zou, Xuefeng; Zhao, Min; Wang, Jingkun; Wang, Xiaoliang; Hao, Yuying; Wang, Hua
Highlights: An efficient HTL is formed by liquid-exfoliated BP nanosheets and PEDOT:PSS, which is demonstrated a simple and effective strategy to form efficient HTL in high-efficiency PSCs. The introduction of BP nanosheets significantly affect the conductivity and aggregation morphology of PEDOT:PSS. The introduction of BP nanosheets dramatically changes the nanostructure of PEDOT:PSS and light absorbers. A champion PCE of 16.41% was obtained in PM6:Y6 light absorber based cell using PEDOT:PSS:BP as the HTL, which is ∼18% efficiency improvement compare to the PSCs that with pure PEDOT:PSS as the HTL. Abstract: Black Phosphorus (BP) has shown great potential in optoelectronic devices due to its remarkable semiconductor properties. Herein, liquid-exfoliated BP nanosheets is doped into poly(3, 4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) to form a hybrid hole transport layers (HTLs). The incorporation of BP nanosheets in PEDOT:PSS dramatically changes the nanostructure and electrical conductivity of film. The BP doped PEDOT:PSS HTLs possess excellent charge selectivity and transport capability, which are proved in non-fullerene and fullerene blend system based polymer solar cells (PSCs). Furthermore, the nanostructure of PM6:Y6 light absorber changes a lot after introduction of BP nanosheets. Thus, weak charge recombination loss, high exciton generation rate and dissociation probability, and low transport resistance are observed in BP nanosheets doped PEDOT:PSS HTLs based cells, which result in improved power conversion efficiency (PCE). As a result, significant improvement of PCE (>18%) is observed in both non-fullerene and fullerene blend systems based cells. This result demonstrates a simple and effective strategy to form efficient HTLs in high-efficiency PSCs.